Effect of support foot placement on football instep kick performance - Ou, Y.-C.; Lei, M. K.; Cheng, K. B. (Science and Medicine in Football, 2023)
Although the support foot plays an important role in kicking a football, there has been a paucity of research exploring the effect of the placement of the support foot on kicking performance. To investigate the kick performance under different support foot positions, ten male footballers were recruited to participate in two experiments: one determining the maximum ball speed and the second determining accuracy. The participants were instructed to plant their support foot on one of nine different spots marked in the form of a 3 × 3 shape on a piece of artificial grass and asked to kick the ball. In the first (maximum speed) test, the participants tried their best to kick the ball at the maximum ball speed from nine different support foot positions. In the second (accuracy) test, the participants kicked the ball toward the target area without restricting the support foot position. The ball speed, as well as the success rate, were recorded from each support foot position. Significantly higher ball speed and accuracy were obtained at medial positions than was the case at lateral positions from the nine spots. It was concluded that although footballers may choose different positions for support foot placement, the maximum ball speed and better accuracy could be expected when the support foot was next to or slightly in front of the ball centre without too much side-by-side separation (27-37 cm).